2019
DOI: 10.3390/jcm8122156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Quality on the Prevalence of Sarcopenia in Older Adults: A Systematic Review with Meta-Analysis

Abstract: Sarcopenia is an age-related condition. However, the prevalence of sarcopenia may increase due to a range of other factors, such as sleep quality/duration. Therefore, the aim of the study is to conduct a systematic review with meta-analysis to determine the prevalence of sarcopenia in older adults based on their self-reported sleep duration. Methods: Three electronic databases were used—PubMed-Medline, Web of Science, and Cochrane Library. We included studies that measured the prevalence of sarcopenia, divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 50 publications
1
24
0
3
Order By: Relevance
“…It was found that 87.0% of the elderly woke up at night and the frequency of night waking was 3 (1)(2)(3)(4)(5)(6)(7)(8). It was determined that the most common reason for waking up at night was the need to use the toilet (60.0%), 60.9% of the participants did not feel rested after sleep, and 98.3% did not perform any practice to fall asleep.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that 87.0% of the elderly woke up at night and the frequency of night waking was 3 (1)(2)(3)(4)(5)(6)(7)(8). It was determined that the most common reason for waking up at night was the need to use the toilet (60.0%), 60.9% of the participants did not feel rested after sleep, and 98.3% did not perform any practice to fall asleep.…”
Section: Re Sultsmentioning
confidence: 99%
“…With ageing, chronic diseases (Hypertension, Chronic Obstructive Pulmonary Disease, Dementia) problems such as fatigue, imbalance, osteoporosis, urinary retention, and disorientation become more common in elderly individuals.In addition, one of the most common problems seen independent of diseases is sleep disorders. 4,5 Wang et al investigated morbidity and symptom prevalence in the elderly and found that elderly individuals mostly experience sleep problems (37.7%). 6 Many studies have reported that individuals aged 65 and over frequently experience sleep problems.…”
mentioning
confidence: 99%
“…The components of cigarette smoke (CS) increase oxidative stress either directly or by activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOXs) in the skeletal muscle tissues that promote phosphorylation of p38 MAPK and activation of NF-kB, which subsequently upregulate muscle-specific E3 ubiquitin ligases that cause muscle degradation [ 13 ]. A recent meta-analysis showed that prevalence of sarcopenia was higher in older adults with inadequate sleep [ 14 ]. Individuals with poor sleep quality show elevated levels of cortisol, a catabolic hormone that promotes protein degradation, and lower levels of IGF-1, an anabolic hormone that promotes protein synthesis, thereby causing increased muscle degradation and loss of muscle mass [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in most of the previous studies which analysed the effect of exercise on sleep quality, endurance training [ 16 , 31 , 35 ] was performed, or the subjects were older in those cases where they studied the effect of RT [ 37 ]. Therefore, it is necessary to continue analysing the effect of RT on sleep quality because previous studies found that lower sleep quality is related to higher prevalence of sarcopenia [ 38 ] and inadequate sleep impairs maximal muscle strength and muscle growth [ 14 ].…”
Section: Discussionmentioning
confidence: 99%